A polarization-sensitive imaging lidar for atmospheric remote sensing. (September 2021) - Kong, Zheng; Ma, Teng; Cheng, Yuan; Fei, Ruonan; Zhang, Zhen; Li, Yichen; Mei, Liang
Highlights: A polarization-sensitive imaging lidar has been proposed and developed for atmospheric polarization studies. The linear volume depolarization ratio as well as the misalignment (offset) angle can be obtained without employing additional optical components and sophisticated system adjustments. A theoretical model describing the methodology has been established and atmospheric validation measurements have been carried out successfully. Abstract: A polarization imaging lidar, employing a linearly polarized continuous-wave 450-nm laser diode and a polarization-sensitive image sensor has been proposed and demonstrated for atmospheric polarization studies. The polarization image sensor, fabricated with four-directional on-chip polarizers at 0°, 45°, 90° and 135°, is able to capture a four-directional polarized image of the laser beam that has been transmitted into the atmosphere, from which four polarized atmospheric backscattering signals with 0°, 45°, 90°, and 135° polarization angles can be simultaneously measured. A theoretical model has been established to retrieve the linear volume depolarization ratio (LVDR) as well as the misalignment (offset) angle between the polarization plane of the transmitted laser beam and the polarization plane of the 0°-directional on-chip polarizer of the image sensor, without employing additional optical components and sophisticated system adjustments. Atmospheric validation measurements have been carried out during a haze event. The promising results have shown a great potential of utilizing the proposed polarization imaging lidar technique for various atmospheric polarization studies.